Fluoropolymers applications in chemical processing industries : the definitive user's guide and databook - Ebnesajjad, Sina (William Andrew Pub., 2005)
This is a self-contained collection of data and information on applications of fluoropolymers components for corrosion control in chemical processing industries. Due to their superior properties, fluoropolymers have been rapidly replacing metal alloys for preserving the purity of processing streams in the chemical processing, plastics, food, pharmaceutical, semiconductor, and pulp and paper industries.
Keywords: Fluoropolymers -- Industrial applications.; elektronické knihy; electronic books